2010
DOI: 10.1186/1743-422x-7-264
|View full text |Cite
|
Sign up to set email alerts
|

An RNA replication-center assay for high content image-based quantifications of human rhinovirus and coxsackievirus infections

Abstract: BackgroundPicornaviruses are common human and animal pathogens, including polio and rhinoviruses of the enterovirus family, and hepatits A or food-and-mouth disease viruses. There are no effective countermeasures against the vast majority of picornaviruses, with the exception of polio and hepatitis A vaccines. Human rhinoviruses (HRV) are the most prevalent picornaviruses comprising more than one hundred serotypes. The existing and also emerging HRVs pose severe health risks for patients with asthma or chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 76 publications
(80 reference statements)
1
38
0
Order By: Relevance
“…Replicating viral RNA was detected by staining double-stranded replicative intermediates and replicative forms with an anti-dsRNA antibody (47). ACBD3 and replicating viral RNA had similar distributions in the perinuclear region of cells at 4 h p.i.…”
Section: Resultsmentioning
confidence: 99%
“…Replicating viral RNA was detected by staining double-stranded replicative intermediates and replicative forms with an anti-dsRNA antibody (47). ACBD3 and replicating viral RNA had similar distributions in the perinuclear region of cells at 4 h p.i.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we had shown that the number of viral particles productively uncoated and the number of cells producing viral antigen are strongly correlated (44). This applies also for the generation of dsRNA produced as a consequence of viral replication and detected with MAb J2 (47). We thus determined the number of infected cells at 16 h postinfection (p.i.…”
Section: Resultsmentioning
confidence: 99%
“…In the experiment with nocodazole, MAb J2 at 1:3,000 (0.66 g/ml; English and Scientific Consulting, Bt. Szirák, Hungary) was applied to detect double-stranded RNA (dsRNA) stemming from replicating virus (47). Numbers of infected cells were determined using TissueQuest software (see above) and normalized to the level in the control (i.e., the percentage of cells infected in the absence of drug was set to 100%).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, cell age after plating (<72 h), inoculum volume (relevant to the culture vessel), medium pH (6.8-7.3), and cell density were important factors for the reproducible appearance of HRV-induced plaques and for higher virus yields [ 48 -51 ]. The HRVs can grow at temperatures above 35 °C (some prefer that under certain conditions) [ 52 ], but rolling at 33 °C, preceded by a 2-4-h stationary incubation period [ 41 ], has historically provided the highest yield and fastest in vitro HRV growth [ 36 , 50 , 53 , 54 ].…”
Section: The Pre-molecular Eramentioning
confidence: 99%